Implementasi Pembelajaran Aqidah Akhlak Pada Peserta Didik di Madrasah Tsanawiyah Mathla’ul Anwar Baros Cibadak - Wahyuni, Siti; Abrori (MAN 1 Kota Kediri, 2023)
Madrasah, as an Islamic educational institution, has a responsibility to equip students with a strong understanding of religion and good morals in accordance with Islamic values. However, the implementation of education in first-degree secondary schools is dominated by general lessons such as IPA and IPS compared to Islamic religious lessons in particular moral studies. Seeing the learning of ethics at the Tsanawiyah Mathla’ul Anwar Baros Cibadak Madrasah is an important step in shaping the character and morals of the pupils. This article aims to investigate how the teaching of equality has been applied in this madrasah with a focus on the pupils. The type of research used in this research is qualitative research that aims to find out how the implementation of Aqidah Akhlak learning at Mathla’ul Anwar Baros MTS Cibadak district of Lebak. The data collection method in this study uses the Observation, Interview, and Documentation methods used in ethical learning. Kata Kunci : Implementasi, Pembelajaran Aqidah Akhlak, Peserta didik. Abstract: This study seeks to see the implementation of learning subjects Aqidah akhlak, the focus of research is how the implementation of learning aqidah akhlak on students at Madrasah Tsanawiyah Mathla'ul Anwar Baros Cibadak, how the results of implementation of learning aqidah akhlak on students at Madrasah Tsanawiyah Mathla'ul Anwar Baros cibadak data collection methods in this study using the method of observation, interview, and documentation methods used in learning aqidah akhlak is the method of lectures, discussions and questions and answers. From the results of interviews with aqidah akhlak teachers that students are so enthusiastic in following this aqidah akhlak learning that students are able to implement this aqidah akhlak learning in their daily lives both in the school environment and outside the school environment. Keywords:Implementation, learning Aqidah morals, learners.